AI and Myths of Creativity. (7th April 2022) - Manovich, Lev
Abstract: Lev Manovich, Director of the Cultural Analytics Lab and Presidential Professor at the City University of New York, explores some of the societal notions surrounding AI and creativity. He exposes certain myths that have grown up around this discourse and posits a wider, more interesting emerging reality.